Differences in gene expression patterns between cultured and natural Haloquadratum walsbyi ecotypes - Rosselli, Riccardo; López-Pérez, Mario; Martin-Cuadrado, Ana-Belen; Rodriguez-Valera, Francisco; Bolhuis, Henk (Frontiers in Microbiology, 2022)
Solar crystallizer ponds are characterized by high population density with a relatively simple community structure in terms of species composition. The microbial community in the solar saltern of Santa Pola (Alicante, Spain), is largely dominated by the hyperhalophilic square archaeon Haloquadratum walsbyi. Here we studied metatranscriptomes retrieved from a crystallizer pond during the winter of 2012 and summer of 2014 and compared Hqr. walsbyi’s transcription patterns with that of the cultured strain Hqr. walsbyi HBSQ001. Significant differences were found between natural and the cultured grown strain in the distribution of transcript levels per gene. This likely reflects the adaptation of the cultured strain to the relative homogeneous growth conditions while the natural species, which is represented by multiple ecotypes, is adapted to heterogeneous environmental conditions and challenges of nutrient competition, viral attack, and other stressors. An important consequence of this study is that expression patterns obtained under artificial cultivation conditions cannot be directly extrapolated to gene expression under natural conditions. Moreover, we found 195 significantly differential expressed genes between the seasons, with 140 genes being higher expressed in winter and mainly encode proteins involved in energy and carbon source acquiring processes, and in stress responses.